Mutations to tolerance and resistance to pesticin and colicins in Escherichia coli phi. - Ferber, D M (1981)
The universal colicin-indicator strain Escherichia coli phi, unlike E. coli strain K-12, is sensitive to pesticin, a bacteriocin produced by wild-type Yersinia pestis. Eleven distinct phenotypes of E. coli phi mutants were obtained by selection for insensitivity to pesticin, group B colicins, the group A colicin S4, or coliphage T5. Representative isolates from eight of these classes closely resembled resistant receptor mutants (Cir-, Fep-, and TonA-) or tolerant mutants (TonB-, ExbB-, ExbC-, Ivt-, and Cmt-) described in Escherichia coli K-12. The remainder were unique; of these, one resembled TonB- but was also tolerant to colicin S4 (TonB/S4-), and the others exhibited specific resistance to either colicin S4 (Sfr-) or to pesticin (Psr-). All receptor mutants except Psr- remained sensitive to pesticin, whereas TonB/S4, TonB-, ExbB-, and ExbC- isolates were highly tolerant to this bacteriocin.